Dsg2-mediated c-Met activation in anaplastic thyroid cancer motility and invasion. Issue 11 (November 2020) - Lee, Kyungmin; Lee, Sang-Hyun; Kim, Wooil; Lee, Jangwook; Park, Jong-Gil; Kim, Jang-Seong; Kim, Jung Tae; Kang, Yea Eun; Shong, Minho; Lee, Hyo Jin; Kim, Jin-Man; Kim, Won Gu; et al.
Abstract : Anaplastic thyroid cancer (ATC) is a rapidly growing, highly metastatic cancer with limited therapeutic alternatives, thus targeted therapies need to be developed. This study aimed to examine desmoglein 2 (Dsg2) expression in ATC and its biological role and potential as a therapeutic target in ATC. Consequently, Dsg2 was downregulated or aberrantly expressed in ATC tissues. ATC patients with low Dsg2 expression levels also presented with distant metastasis. Dsg2 depletion significantly increased cell migration and invasion, with a relatively limited effect on ATC cell proliferation in vitro and increased distant metastasis in vivo . Dsg2 knockdown induced cell motility through the hepatocyte growth factor receptor (HGFR, c-Met)/Src/Rac1 signaling axis, with no alterations in the expression of EMT-related molecules. Further, specific targeting of c-Met significantly inhibited the motility of shDsg2-depleted ATC cells. Decreased membrane Dsg2 expression increased the metastatic potential of ATC cells. These results indicate that Dsg2 plays an important role in ATC cell migration and invasiveness. Therapies targeting c-Met might be effective among ATC patients with low membrane Dsg2 expression levels, indicating that the analysis of Dsg2 expression potentially provides novel insights into treatment strategies for ATC.